SRDD: a lightweight end-to-end object detection with transformer - Zhu, Yuan; Xia, Qingyuan; Jin, Wen (Connection science, 2022)
Computer vision is now playing a vital role in modern UAV (Unmanned Aerial Vehicle) systems. However, the on-board real-time small object detection for UAVs remains challenging. This paper presents an end-to-end ViT (Vision Transformer) detector, named Sparse ROI-based Deformable DETR (SRDD), to make ViT model available to UAV on-board systems. We embed a scoring network in the transformer T-encoder to selectively prune the redundant tokens, at the same time, introduce ROI-based detection refinement module in the decoder to optimise detection performance while maintaining end-to-end detection pipeline. By using scoring networks, we compress the Transformer encoder/decoder to 1/3-layer structure, which is far slim compared with DETR. With the help of lightweight backbone ResT and dynamic anchor box, we relieve the memory insufficient of on-board SoC. Experiment on UAVDT dataset shows the proposed SRDD method achieved 50.2% mAP (outperforms Deformable DETR at least 7%). In addition, the lightweight version of SRDD achieved 51.08% mAP with 44% Params reduction.